Theorems on the average values and non-oscillating character of the solutions of the partial differential equations in the spaces $E^n$ and $P^n$ - Bugir, M.K. (Ukrains’kyi Matematychnyi Zhurnal, 2024)
Analogs of the mean-value theorem are obtained for the Poisson equation with the Laplace-Beltrami operator in Euclidean and spherical spaces.